Mithra at Hatra? Some remarks on the problem of the Irano-Mesopotamian syncretism - Drijvers, H. J. W.
against the theory of Fr. Cumont, R. Dussaud, G. Widengren that Ahura-Mazda was assimilated to Bel, Anahita to Ishtar, Mithra to Shamash.